2013
DOI: 10.1002/imhj.21425
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Changes in Parenting Self-Efficacy: Linkages With Anxiety and Depressive Symptoms in Primiparous Women

Abstract: The aim of the study was to examine parenting self-efficacy in relation to depressive and anxiety symptoms during pregnancy. Five hundred thirty-three first-time pregnant women completed questionnaires at 12, 22, and 32 weeks of pregnancy that measure parenting self-efficacy, anxiety, and depressive symptoms. Parenting self-efficacy increased slightly but significantly over the course of pregnancy. Higher levels of depressive symptoms as well as state and trait anxiety symptoms were related to lower expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
6
35
0
Order By: Relevance
“…[ 15 16 ] Studies have shown anxiety is more frequent in nulliparous women who are pregnant for the first time. [ 7 17 ] …”
Section: Introductionmentioning
confidence: 99%
“…[ 15 16 ] Studies have shown anxiety is more frequent in nulliparous women who are pregnant for the first time. [ 7 17 ] …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that low PSE seems to be correlated with parental depression, anxiety, defensive and controlling parental strategies, high levels of parental stress, passive coping and feelings of helplessness in the parenting role, and the use of punitive disciplinary techniques (Jones & Prinz, ; Salonen et al, ; Wernand, Kunseler, Oosterman, Beekman, & Schuengel, ). Most of these results were derived from cross‐sectional studies.…”
mentioning
confidence: 99%
“…Most of these results were derived from cross‐sectional studies. Among studies that have adapted longitudinal data, Wernand et al () found that during the course of pregnancy, depression, anxiety, and PSE were strongly linked, but only anxiety symptoms predicted later PSE. Jones and Prinz () stated that it was unclear whether PSE functioned consistently as an antecedent or contributor to parental depression, as a consequence of parental depression, or in a transactional relationship with parental depression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, few studies have been conducted about women's experiences and perceptions of MHRP, especially in the United States (Rubarth, Schoening, Cosimano, & Sandhurst, ), despite the fact that 3 to 10% of U.S. pregnancies (dependent upon diagnosis) are deemed medically high‐risk (National Institute of Child Health Development, ). In addition, there is ample evidence that maternal prenatal experiences influence the nature of a mother's attachment to her infant once she or he is born and subsequent infant mental health (Huth‐Bocks, Theran, Levendosky, & Bogat, ; Wernand, Kunseler, Oosterman, Beekman, & Schuengel, ). Our research aim was to systematically explore such women's experiences during MHRP.…”
mentioning
confidence: 99%